Involvement of people with dementia in raising awareness and changing attitudes in a dementia friendly community pilot project. (November 2019) - Phillipson, Lyn; Hall, Danika; Cridland, Elizabeth; Fleming, Richard; Brennan-Horley, Chris; Guggisberg, Nick; Frost, Dennis; Hasan, Helen
Low levels of public understanding can contribute to the fear, stigma and social exclusion associated with living with dementia. Dementia friendly communities aim to address this by empowering people with dementia and increasing their social inclusion. As a part of a Community Based Participatory Action Research (CBPAR) process, a multicomponent dementia friendly community intervention supported: research; the establishment of a Dementia Advisory Group and Alliance; an awareness campaign and education in community organisations. Educational events were co-designed and co-facilitated by people with dementia and their care partners. To assess project reach and changes in attitudes of community members, two cross sectional surveys were conducted with adults (aged over 18 years) using validated scales. Independent samples t -tests compared responses to the surveys prior to the commencement of the project (2014) and two years later (2016). In 2016, respondents showed increased agreement with the statements: 'People with dementia participate in a wide variety of activities and interests, ' and, 'It is easy to find out about dementia friendly services or organisations in Kiama'. Respondents who attended an educational event reported less negative views about how they themselves would feel if they were diagnosed with dementia compared with respondents who did not attend an event. CBPAR appears useful to support the involvement of people with dementia and the engagement of the community to improve awareness of dementia services. The direct involvement of people living with dementia as spokespeople and educators was an effective way to improve positive attitudes and reduce the negative stereotypes associated with living with dementia. Further research is needed to compare different approaches to the creation of dementia friendly communities in different locations, and to establish the extent to which local interventions are useful to complement efforts to raise awareness of dementia at a national level.